Exploiting non-linear scales in galaxy–galaxy lensing and galaxy clustering: A forecast for the dark energy survey. Issue 4 (4th January 2022) - Salcedo, Andrés N; Weinberg, David H; Wu, Hao-Yi; Wibking, Benjamin D
ABSTRACT: The combination of galaxy–galaxy lensing (GGL) and galaxy clustering is a powerful probe of low-redshift matter clustering, especially if it is extended to the non-linear regime. To this end, we use an N -body and halo occupation distribution (HOD) emulator method to model the redMaGiC sample of colour-selected passive galaxies in the Dark Energy Survey (DES), adding parameters that describe central galaxy incompleteness, galaxy assembly bias, and a scale-independent multiplicative lensing bias A lens . We use this emulator to forecast cosmological constraints attainable from the GGL surface density profile ΔΣ( rp ) and the projected galaxy correlation function wp, gg ( rp ) in the final (Year 6) DES data set over scales $r_p=0.3\!-\!30.0\, h^{-1} \, Mpc$ . For a $3{{\ \rm per\ cent}}$ prior on A lens we forecast precisions of $1.9{{\ \rm per\ cent}}$, $2.0{{\ \rm per\ cent}}$, and $1.9{{\ \rm per\ cent}}$ on Ω m, σ8, and $S_8 \equiv σ _8Ω _m^{0.5}$, marginalized over all halo occupation distribution (HOD) parameters as well as A lens . Adding scales $r_p=0.3\!-\!3.0\, h^{-1} \, Mpc$ improves the S 8 precision by a factor of ∼1.6 relative to a large scale ($3.0\!-\!30.0\, h^{-1} \, Mpc$ ) analysis, equivalent to increasing the survey area by a factor of ∼2.6. Sharpening the A lens prior to $1{{\ \rm per\ cent}}$ further improves the S 8 precision to $1.1{{\ \rm per\ cent}}$, and it amplifies the gain from including non-linear scales. Our emulator achieves per cent-level accuracy similar to the projected DES statistical uncertainties, demonstrating the feasibility of a fully non-linear analysis. Obtaining precise parameter constraints from multiple galaxy types and from measurements that span linear and non-linear clustering offers many opportunities for internal cross-checks, which can diagnose systematics and demonstrate the robustness of cosmological results.